Membaca Dan Menafsirkan Temuan Gambar Prasejarah Di Pulau Misool Raja Ampat, Papua Barat - Nasrudin Nasrudin (Balai Arkeologi Sumatera Utara, 2015)
Traces and evidence of prehistoric civilization in the Indonesian Archipelago have been found, and one of the archaeological types of remains that was the hot topic for researchers nowadays is rock paintings on the walls of karst caves (known as limestone area). We found that karst has the function of conveying historical messages through paintings as a form of communications of Homo sapiens. Based on results of surveys among the karst island of Misool in Raja Ampat islands, we can identify five categories of rock paintings, which are: hands, fauna, anthropomorphic, symbolical (non-figure), circles that resemble wheels/the sun, and square lines. The main and dominant characteristics of Misool rock paintings, particularly in paintings of fish, are their various sizes and rich variations. The prehistoric artworks are very interesting to be investigated more thoroughly to study and understand better the human life in the past. The archaeological survey has yielded new evidence and traces of human life in the past, such as habitation, migration, and modes of living hundreds or maybe even tens of thousand years ago, or during the prehistoric period. This research is the initial step and was carried out using documentation and descriptive methods to be analyzed afterward by various approaches that are being developed nowadays, as well as visual communication through form and non-form analyses.